Ranking of academic graduate programs in Brazil in the period 2010-2012 - DOI: http://dx.doi.org/10.16930/2237-7662/rccc.v15n46p74-87 - Soares, Sandro Vieira (2016)
This article aims to analyze the performance of Brazilian accounting graduate programs in the 2010-2012 period based on the bibliographic production published in scientific journals. For these, five indicators were analyzed: the total score of the graduate program, the average score per professor, the variation coefficient of scientific production, the percentage of productive professors and the international integration level. Our sample is composed of only academic graduate programs. In this sense, the professional programs were not analyzed due to their different objectives. The data about the bibliographic production of programs and professors were obtained from the three-year Capes evaluation of 2013 and from the analysis of the Lattes curriculum of professors. Our results showed that: (i) in the total score item, the institutions that performed better were FURB, USP and UFSC; (ii) with regard to international integration, the institutions that performed better were USP, FUCAPE and UFSC; (iii) programs with the highest average scores for professors are UFSC, FURB and UFES, (iv) regarding the dispersion of the production of professors (coefficient of variation), the institutions with better performance were FUCAPE, UNB and USP and (v) FURB, UFSC, UNB and FUCAPE had the highest proportion of professors who were considered productive in the three-year Capes evaluation.